POLA PEMANFAATAN PERIKANAN TANGKAP DI KAWASAN KONSERVASI PERAIRAN KABUPATEN CIAMIS - Endratno, Endratno; Simbolon, Domu; Wiryawan, Budy; Yusfiandayani, Roza (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Utilization of fishing area in marine protected area in Ciamis waters by various activities may cause multi sectors conflict related to management of the Ciamis waters. The integrated zone system in that area has not been established yet, therefore it is needed to be studied. This paper aimed to analyze resources use of capture fisheries on Marine Protected Area in Ciamis waters. This research used spatial analysis approach for overlaying fishing ground area and other use. The result showed the rules of fishing lines and placement of fishing gear, fishing grounds and the existing zonation. Utilization of fish resources was appropriate in the zone, but fishing gears that still could triger social conflict and its operations did not fit with the sustainable utilization mechanisms. Fishing areas predominantly in coastal areas that need to be developed to encourage the fishermen fishing outside the coastal region.